FORMING THE CHARACTER OF DISCIPLINE AND LEARNING MOTIVATION WITH CREATIVITY THROUGH MAKING A WISHING TREE PROFILE PANCASILA STUDENTS - Zul Fahriyanto Abubakar; Yayuk Sulastri; Nurlisa N. Sid; Nur Anisah S. Musa; Mahdania D. S.; Abdul Rahmat (International Journal of Innovations in Engineering Research and Technology, 2022)
From the activity of making a wishing tree project, positive things that can be obtained are that it can form the disciplined character of students, motivate them to be creative through wishing trees. besides that the positive things that are also obtained are being able to establish and build collaboration between students and students to both complete the wish tree properly and according to what is desired. The values that can be learned in the activity of making a wishing tree project are the values of humanity and cooperation, in which in making a wishing tree the students work together to finish making a wishing tree. The value of creativity, the value of creativity that is obtained is that students can be creative through making wish trees by cutting cardboard paper and decorating tree branches so that they become beautiful wish trees. Discipline value, the discipline value obtained is that students can become more disciplined and not neglect education so they can reach the goals they want to achieve.